A Compact 38 GHz millimeter Wave MIMO Antenna Array for 5G Mobile Systems - Tahat, Ashraf; Ersan, Bandar; Al-Muhesen, Laith; Shakhshir, Zaid; A.Edwan, Talal (Journal of Telecommunications and the Digital Economy, 2020)
This paper presents the design of a compact 2´ x 2 microstrip antenna array of size 11.9 ´15.3 mm2 operating at the mm-Wave of 38 GHz. We achieved a high gain of 14.58 dB, a return loss of -17.7 dB, and a wide impedance bandwidth of 500 MHz. This antenna is duplicated twelve times around an angle of 30° forming a low-profile dodecagon. Each sector can cover a beam of 58° to obtain 12 beams covering the 360 degrees. When compared with implemented antenna designs in the literature that target similar features of com-pact size and low-profile at the desired 5G frequency of 38 GHz, our design had a noticeable reduction in size with an increased gain. Our designed antenna is suited for MIMO beamforming, or switched beam technology applications in mobile wireless systems that include miniaturized base stations or moving network systems, such as mobile hotspots or vehicular networks and related elements .